Web systems engineering for prioritization of research area INFSKM / Anitawati Mohd Lokman - Mohd Lokman, Anitawati (Research Management Institute (RMI), 2012)
Faculty of Computer Science and Mathematics run various forms of research and projects namely the degree level Final Year Project, theses and Dissertation for the Masters and Ph. D programs, Independent Studies, class projects, lecturers' project, research and consultancy, and Industrial Training. There are many duplications, uncoordinated works, intersections, and no lesson learnt happening. There seem no serious effort to integrate these works to form bigger projects needed by students and lecturers for case exercises and studies. These cases can become very useful. At the same time, there are plenty of rooms to improve the faculty operations. There were some projects that did dwell on creating computerised processes but they were not properly packaged nor designed. One main factor is due to limited time allocated for each project. They are normally given one semester to be completed. Secondly, all projects are treated individually. One objective of this project is to align the research and works for building automated office systems for the faculty by coming up with research frameworks as a guide for lecturers and students. It is envisioned that each project must be adequately designed, developed, tested, documented and deployed. The questions arise are how should projects be prioritised, sequenced and approached as a group.